(untitled) (Journal of Education and Development, 2022)
The arrival of the era of big data has promoted the new reform and development of various social industries, especially providing opportunities and challenges to improve the effectiveness of party history education in college students. At present, there are major problems in the party history education of college students, such as weak awareness of big data application, lack of big data application ability, imperfect party history education management system and the need to expand the party history education data platform to be expanded. Because of the problem, the corresponding countermeasures are put forward from establishing the concept of big data, building high-quality big data teachers, improving the big data management system of party history education for college students, and actively expanding the party history education big data platform.